3D-Printed lightweight ceramics using capillary suspensions with incorporated nanoparticles. Issue 8 (July 2020) - Weiß, Moritz; Sälzler, Patrick; Willenbacher, Norbert; Koos, Erin
Abstract: A new versatile route is reported to produce tailored porous sintering materials with high mechanical strength. A self-assembly mechanism deposits trace amounts of nanoparticles at contact areas between coarse ceramic particles prior to sintering, resulting in large and uniformly dense sintering bridges. This increases the porosity up to 75 % and simultaneously offers higher mechanical strength in comparison to similar materials even when weaker silica nanoparticles are introduced. This route is ideally suited for robocasting as well as conventional extrusion and, thus, can be used for rapid prototyping and mass production. We report the highest compressive strength-to-weight ratios for lightweight macroporous ceramics, covering an unrivaled density range while offering exceptional flexibility in tailorable microstructure. The strength is dominated by the silica bridges and identical strength is achieved for alumina and aluminosilicate structures. Finally, this route can be used to build hierarchical structures by point-welding particles while preserving inner surface area.